"God always provides": Challenges and barriers in food assistance delivery in Mississippi. Issue 1 (1st January 2018) - Johnson, Kecia R.; McKinley, Kenya; Hossfeld, Leslie; Oliver, Brittney; Jones, Claudette; Kerr, Laura Jean; Trinh, Maria
Abstract: This exploratory research project identifies critical needs for food pantry delivery in rural Mississippi. Our study describes the experiences of food pantry operators and volunteers while documenting the challenges these pantry providers encounter when attempting to meet the needs of pantry patrons. We interviewed 25 food pantry providers/volunteers at 14 food pantries located in nine counties in Mississippi, representing four geographic areas of the state (North Central, Central, Delta (West), and Southwest). Findings suggest that growing demand for services, coupled with stricter reporting requirements and infrastructure barriers are key challenges that food pantry service providers face. These issues are important to community development studies that focus on how coalition building facilitates community partnerships that support food assistance programs.